2007
DOI: 10.22358/jafs/66796/2007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary herbs and coral mineral complex on growth performance, nutrient digestibility, blood characteristics and meat quality in finishing pigs

Abstract: Eighty crossbred pigs of initial mean body weight 58 kg were used to evaluate the effect of supplemental herbs and coral mineral complex (HC) on growth performance, nutrient digestibility, blood characteristics and meat quality in a 8 weeks growth trial. Pigs were randomly allocated to 4 treatments, which comprised: 1. control, 2. HC 0.05%, 3. HC 0.1%, and 4. HC 0.2%, respectively (4 pigs/pen, 5 replicates/treatment). Gain/feed linearly increased during week 4-8 (P<0.05) and overall period (P<0.10) with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…Therefore, it can be concluded that the HEM (S. baicalensis and L. japonica) used in this study may play a key role in reducing stress in pigs. In accordance with the present study, Wang et al (2007) reported that the inclusion of herbs could linearly decline serum cortisol level in finishing pigs. It has been demonstrated that a large group of plant-derived compounds in herbs, such as alkaloids, flavonoids, phenolics, and essential oils possess antistress, tranquilising and sedative properties (Pei 1991).…”
Section: Blood Profilessupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, it can be concluded that the HEM (S. baicalensis and L. japonica) used in this study may play a key role in reducing stress in pigs. In accordance with the present study, Wang et al (2007) reported that the inclusion of herbs could linearly decline serum cortisol level in finishing pigs. It has been demonstrated that a large group of plant-derived compounds in herbs, such as alkaloids, flavonoids, phenolics, and essential oils possess antistress, tranquilising and sedative properties (Pei 1991).…”
Section: Blood Profilessupporting
confidence: 93%
“…Yan et al (2011b) also demonstrated that a complex herbal extract powder has a positive effect on BW, ADG and ADFI in finishing pigs. In contrast, lack of effects of herbs or their extract supplementation on growth performance in finishing pigs was observed by Wang et al (2007) and Ao et al (2011). These inconsistency results may be due to the selection of particular herb materials, forms of their administration (herbal plants, herbal extracts or oils), the amount of herbs, as well as the interactive of different herbs (Frankič et al 2009).…”
Section: Growth Performancementioning
confidence: 99%
See 2 more Smart Citations
“…During the last decades, phytogenic feed additives have been wildly used as an alternative to antibiotics because of their plant-derived property and growth-promoting effects (Hong et al 2004;Wang et al 2007;Wang et al 2008;Windisch et al 2008;Jang et al 2010;Ao et al 2011). Valchev et al (2009) demonstrated that herbal extracts (150 mg/kg) in pig diet could increase growth performance, feed efficiency, and immune-related blood characteristics.…”
Section: Introductionmentioning
confidence: 99%